1991
DOI: 10.1111/j.1600-051x.1991.tb00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and structural characteristics of periodontal tissues in young and old dogs

Abstract: The aim of this study was to examine some clinical and structural features of healthy periodontal tissues in young and old beagle dogs. The material consisted of 10 beagle dogs; group I (1-year old) and group II (8-9 years of age). All animals belonged to the same beagle dog colony and had been carefully monitored from birth. A given day was termed day 0 on which the teeth of all 10 dogs were scaled and polished and a 6-week period of enhanced plaque control was initiated. On day 42, clinical examinations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 29 publications
1
40
1
4
Order By: Relevance
“…It has also been reported that the average diameters of collagen fibrils in the periodontal ligament at three root levels of human extracted teeth remain constant (54 -59 nm) from 10 -75 years of age (Luder et al, 1988). By contrast, the volumes of collagen in the supracrestal connective tissues and the periodontal ligament adjacent to the bone crest are significantly larger in old dogs (8 -9 years old) than in young dogs (1 year old) (Berglundh et al, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…It has also been reported that the average diameters of collagen fibrils in the periodontal ligament at three root levels of human extracted teeth remain constant (54 -59 nm) from 10 -75 years of age (Luder et al, 1988). By contrast, the volumes of collagen in the supracrestal connective tissues and the periodontal ligament adjacent to the bone crest are significantly larger in old dogs (8 -9 years old) than in young dogs (1 year old) (Berglundh et al, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…The significance of these findings could mean an increase in epithelial permeability to bacterial antigens, a decreased resistance to functional trauma, or both, which might influence long-term periodontal outcomes. However, other studies have found no age-related differences in the gingival epithelium of humans or dogs [2]. Other reported changes with aging include the flattening of rete pegs and altered cell density.…”
Section: Changes In the Tissues Of The Periodontium With Age Gingivalmentioning
confidence: 91%
“…Some reports show migration of the junctional epithelium from its position in healthy individuals (i.e., on enamel) to a more apical position on the root surface with accompanying gingival recession [2]. However, in other animal studies, no apical migration has been noted [3].…”
Section: Changes In the Tissues Of The Periodontium With Age Gingivalmentioning
confidence: 99%
“…What was once thought to be passive eruption during the teens is really active eruption, compensating for the vertical jaw growth occurring at that time. Some reports show migration of the junctional epithelium from its position in healthy individuals (i.e., near the CEJ) to a more apical position on the root surface, with accompanying gingival recession [27]. In other animal studies, however, no apical migration has been noted [28].…”
Section: Attrition and Eruption Effectsmentioning
confidence: 99%